Study of Actinobacteria and their Secondary Metabolites from Various Habitats in Indonesia and Deep-Sea of the North Atlantic Ocean ... : Untersuchung von Actinobakterien und ihren Sekundärmetaboliten aus verschiedenen Lebensräumen in Indonesien und der Tiefsee des Nordatlantiks ... - Risdian, Chandra (Universitätsbibliothek Braunschweig, 2020)
Actinobacteria are Gram-positive bacteria and the prolific producers of bioactive molecules. In the course of drug discovery from actinobacterial sources, some samples were taken from different locations and habitats of Indonesia and isolation of Actinobacteria was conducted thereof. Totally 196 strains of Actinobacteria were isolated, and approximately half of them were characterized by 16S rRNA gene analysis. Around two-thirds of them were detected as Streptomyces. One of the Streptomyces strains, i.e., strain SHP 1-2 produced active extracts against some microbial pathogens. Analysis and isolation of compounds from its extract revealed that two novel molecules, which are indolactam derivatives, were found from it. Polyphasic taxonomy study of strain SHP 1-2 suggested that this strain is a novel species in the Streptomyces group. Another study from different strains suggested that strain MAE-11, isolated from mangrove area, was identified close to Kitasatopora and Streptomyces species and generated active ... : Actinobakterien sind Gram-positive Bakterien und die ergiebigsten Produzenten bioaktiver Moleküle. Im Zuge der Wirkstoffforschung aus Actinobakterien wurden einige Proben an verschiedenen Orten und Lebensräumen Indonesiens entnommen und daraus Actinobakterien isoliert. Insgesamt wurden 196 Aktinobakterien-Stämme isoliert und etwa die Hälfte von ihnen wurde durch 16S-rRNA-Genanalyse charakterisiert. Etwa zwei Drittel von ihnen wurden als Streptomyces identifiziert. Einer der Streptomyces-Stämme, d. h. Stamm SHP 1-2, produzierte aktive Extrakte gegen einige pathogene Mikroorganismen. Nach Analyse und anschließender Isolierung der Inhaltsstoffe konnten zwei neue Substanzen, die zu der Indolactam-Derivaten gehören, gefunden werden. Eine polyphasische Taxonomiestudie des Stammes SHP 1-2 legte nahe, dass dieser Stamm zu einer neuen Spezies in der Gattung Streptomyces-gehört. Eine vergleichende Studie mit verschiedenen Stämmen legte nahe, dass der Stamm MAE-11, der aus Mangrovengebieten isoliert wurde, nahe ...